Digital storytelling as an interdisciplinary project to improve students' English speaking and creative thinking. Issue 4 (4th May 2022) - Yang, Ya-Ting Carolyn; Chen, Yi-Chien; Hung, Hsiu-Ting
Abstract: The present research examined the effectiveness of digital storytelling (DST) on foreign language learners' English speaking and creative thinking. In this study, DST was realized in the form of an interdisciplinary project integrated in a partnership between an English course and a computer course, with the class time of the former devoted to the content design and that of the latter to the multimedia design of learner-generated digital stories. The participants were required to work in small groups to create their digital stories in the target language, English, under an eight-week interdisciplinary curriculum. A two-group quasi-experiment with a pretest and posttest design was then conducted to compare the participants' learning outcomes. The findings reveal the authentic and meaningful learning opportunities that DST has to offer for effectively fostering the students' development of becoming proficient English speakers and creative thinkers. Future implementations on interdisciplinary DST projects are thus recommended for educators.